Zr‐MOF Combined with Nanofibers as an Efficient and Flexible Capacitive Sensor for Detecting SO2. Issue 10 (2nd July 2021) - Zhang, Xiuling; Zhai, Zhenyu; Wang, Jiaona; Hao, Xiaoke; Sun, Yaxin; Yu, Shuyan; Lin, Xiaoqiu; Qin, Yue; Li, Congju
Abstract: The fabrication of gas sensors with flexible properties and sensitive performances is of great importance for improving wearable sensing electronics. Herein, we coated a metal‐organic framework (UiO‐66‐NH2 ) on flexible electrospun polyvinylidenefluoride (PVDF) nanofibers as sensing layer for real‐time monitoring of toxic SO2 at room temperature. The developed capacitive sensor possesses a great bending flexibility, excellent cycling stability, high detection sensitivity, light weight as well as portable ability. The fabricated sensor possesses a short response time with 435 s and 185 s towards 150 ppm and 1 ppm, respectively. Importantly, the flexible sensor still maintained outstanding sensing behavior with the retention value of 98.4% in the detection of SO2 at 10 ppm after bending 2000 times. In addition, significant cycling performance was desirably achieved, and the response value of the sensor was also kept at about 88.7% towards 50 ppm SO2, compared with original sensor after 20 days. This strategy can provide promising applications for the development of wearable devices for the detection of harmful gases. Abstract : A flexible capacitive sensor based on a UiO‐66‐NH2 /PVDF nanofiber membrane (NM) for SO2 sensing is reported. UiO‐66‐NH2 is used as dielectric layer, and the PVDF NM provides a flexible substrate and diffusion layer. An excellent sensitivity performance and remarkable stability under normal and bending conditions are both achieved.